Fostering global partnerships: Finite Element Method application workshop in collaboration with Universitas Gadjah Mada, Indonesia / Noorsuhada Md Nor … [et al.] - Md Nor, Noorsuhada; Mat Saliah, Soffian Noor; Md Hasan, Ahmad Syauqi; Jamaludin, Amril Hadri; Fauzi, Mohd Azrizal; Ruslan, Amir Khomeiny; Hashim, Khairul Afinawati; Setiawan, Angga Fajar (UiTM Global @ Office of International Affairs, 2024)
February 2, 2023, a five-day workshop served as a platform for knowledge sharing, aimed at enhancing the skills of several students from the Civil Engineering Studies in using the Abaqus application and the Finite Element Method. This initiative sought to improve the quality of final-year students' research in simulation analysis using Abaqus. The programme aligns with the vision of Dato’ Prof. Ts. Dr. Hajah Roziah Mohd Janor, Vice-Chancellor of UiTM, to promote activities that foster research advancement, ensuring alignment with international research standards and strengthening UiTM's global presence through student research capabilities. It also reflects the university's philosophy, encouraging individuals to excel through knowledge transfer for the betterment of self, society, and the nation.